Methods of aircraft fuel system protection against low-temperature failures of its serviceability - Максютинський, П. Ф.; Козаченко, О. І.; Туз, М. Д. (Proceedings of National Aviation University (archive), 1999)
The following aircraft fuel system protection methods against low-temperature failures of its serviceability have been considered: the method of fuel temperature stabilization in the tanks at a predetermined level, also method of hydrocleaning of low-temperature deposits from the fuel pump filter. By the application of calculations and experimental research we have determined parameters of the system for the fuel temperature stabilization by means of utilization of heat at the radiator of the air-conditioning system and the effectiveness of the hydrocleaning of low-temperature deposits. The design of punched collector and the effective modes of hydrocleaning have been proposed